ConVarT: a search engine for matching human genetic variants with variants from non-human species. Issue Volume 50:Issue D1(2022) (28th October 2021) - Pir, Mustafa S; Bilgin, Halil I; Sayici, Ahmet; Coşkun, Fatih; Torun, Furkan M; Zhao, Pei; Kang, Yahong; Cevik, Sebiha; Kaplan, Oktay I
Abstract: The availability of genetic variants, together with phenotypic annotations from model organisms, facilitates comparing these variants with equivalent variants in humans. However, existing databases and search tools do not make it easy to scan for equivalent variants, namely 'matching variants' (MatchVars) between humans and other organisms. Therefore, we developed an integrated search engine called ConVarT (http://www.convart.org/ ) for matching variants between humans, mice, and Caenorhabditis elegans . ConVarT incorporates annotations (including phenotypic and pathogenic) into variants, and these previously unexploited phenotypic MatchVars from mice and C. elegans can give clues about the functional consequence of human genetic variants. Our analysis shows that many phenotypic variants in different genes from mice and C. elegans, so far, have no counterparts in humans, and thus, can be useful resources when evaluating a relationship between a new human mutation and a disease.